PENGARUH DISIPLIN KERJA DAN STRES KERJA TERHADAP KINERJA GURU DENGAN MEDIASI KOMITMEN ORGANISASI DI SMK FARMASI DI KOTA SEMARANG ( Studi pada SMK Farmasi di Kota Semarang ) - Dwi Antari Dyah Sakuntala wati, 11.52.02.0014 (Students Journal of Economic and Management, 2013)
The study is intended examine and analyze the influence of work discipline and work stress toward the teacher performance by mediation of organization commitment at Pharmasy vocational High School in Semarang. Sampling technique are non probability sampling, purposive sampling with 120 teachers ,technique data test are validity test, reliability test, double linear regression and partial hypothesis with t- test, simultant test with F test and mediation test by Sobel test. The research proves that work discipline, is significant and has positive influence toward the teacher performance, whilework stress has negative influence toward teacher performance from mediation test by using sobel testis shows that organization commitment dnot mediate work discipline toward Teacher Performance.while organization commitment can mediate work stress toword teacher performance at vocational high school in Semarang It means work dicipline is more efective in influencing directly toward teacher performance than by controlling organization commitment. Keywords : Work discipline, Work stress, Organization commitment, and teacher Performance.